Growth Failure in Thalassemia Major Patients in Samples of Iraqi Patients - Shaima’A Dakhel ABDULHASSAN (Modern Medicine)
Introduction: Thalassemia, a hereditary autosomal recessive blood disorder, arises from genetic abnormalities leading to a diminished synthesis rate of one of the globin chains constituting hemoglobin. The integration of transfusion and chelation therapies has significantly elongated the lifespan of individuals diagnosed with thalassemia. This study aims to understand growth failure among individuals with beta-thalassemia major when compared to typically developing children of similar age groups. Additionally, the research explores the potential hormone treatment requirement in this situation. Methods: Between November 1, 2019, and June 7, 2020, case-control research was carried out at the Thalassemia Centre of the Maternity and Children Hospital in Diwaniyah. The dataset included data from 100 thalassemic patients receiving blood transfusions and normal follow-up visits at the hospital. The patients ranged in age from 5 to 15 years. In addition, data were collected from 100 individuals without thalassemia, also within the same age range. Collected data encompassed age, gender, height, and weight, evaluated using the clinical growth chart from CDC. Further details recorded included the frequency of blood transfusions, the chelating agent used, serum ferritin levels, and hormone levels. Results: We discovered that, with a P value less than 0.0001, there is a significant difference in normal weight between healthy children and beta thalassemic patients. Additionally, the healthy children were found to be taller than the beta thalassemic patients. Conclusion: The study has revealed that the growth failure rate is directly linked to recurrent blood transfusion, and iron overload & resulting endocrine dysfunction.